Pengaruh Penggunaan PS Ball Sebagai Pengganti Pasir Terhadap Kuat Tekan Beton - Ronald Simatupang; Naning Dyah Ulfaturosida (Jurnal Teknik Sipil, 2014)
Development in the current structure is progressing very rapidly which took place invarious fields. Concrete is one option as a structural material in building construction. But withincreasing climate change needs an innovation in the world of construction to be able to create aconcrete constituent materials friendly to the environment. One way to use the waste products ofsteel called a PS Ball. The purpose of this research is to knowing the effect of using PS Ball as areplacement of sand in to compressive strength. Result obtained from research performed is thatthe PS Ball can use as the replacement of sand in the mix concrete. The increase in compressionstrength of concrete when PS Ball as sand replacement is 1,16 from normal concrete.